Hard carbon with molecular sieve type closed cell structure as anode

By performing specific heat treatment on the biomass mixture, a hard carbon material with a molecular sieve type closed-cell structure is formed, which solves the problem of poor electrochemical performance of hard carbon materials in the prior art, and achieves high performance of sodium ion batteries.

CN119604994AInactive Publication Date: 2025-03-11HONG KONG APPLIED SCI & TECH RES INST

Patent Information

Application Number
CN202480002937.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-10-23
Filing Date
2024-10-31
Publication Date
2025-03-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When used in sodium ion battery anode, existing hard carbon materials lack effective pore structure control, resulting in poor electrochemical performance.

Method used

By performing a two-step heat treatment on the biomass mixture, including calcining at 300-600°C and recalcining at 900-1400°C, a hard carbon material with a molecular sieve type closed-pore structure is formed.

Benefits of technology

The optimized structure of hard carbon materials is achieved, the embedded and detachment kinetics of sodium ions are improved, and the cycle stability and energy density of sodium ion batteries are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119604994A_ABST
    Figure CN119604994A_ABST
Patent Text Reader

Abstract

The invention discloses hard carbon with a molecular sieve type closed-pore structure and a preparation method thereof.The preparation method comprises the steps that a biomass mixture such as cotton and crop waste serves as a raw material, or a mixture containing 70-90% of cellulose, 9-20% of hemicellulose, 1-10% of lignin and the like serves as a raw material, calcination is conducted at the temperature of 300-600 DEG C, and a pre-carbonized precursor is obtained; and then cleaning the precursor with an alkali solution, and finally carrying out secondary calcination at 900-1400 DEG C to obtain a hard carbon product with a molecular sieve type closed pore structure.
Need to check novelty before this filing date? Find Prior Art

Description

Background Art

[0001] The present invention relates to hard carbon having a molecular sieve type closed-pore structure and a method for producing the same.

[0002] In recent years, sodium-ion batteries (SIBs) have attracted much attention as a promising alternative to lithium-ion batteries, especially due to the abundance and widespread supply of sodium. However, the performance of sodium-ion batteries depends largely on the quality of the anode material, which must accommodate the larger radius of sodium ions than lithium ions and allow for fast ion transport.

[0003] Hard carbon is widely used as an active anode material for SIBs. Due to its low price, hard carbon is the best choice for SIBs anode. The structure of hard carbon includes short carbon chains, highly disordered structure, long interlayer spacing and closed pore structure. Hard carbon is a non-graphitic carbon with an amorphous structure with a certain degree of short-range order. Since this structure can accommodate sodium ions, it is particularly suitable for energy storage applications.

[0004] Traditionally, hard carbons from various carbon sources have been used as anode materials for SIBs, but often result in suboptimal electrochemical performance due to the lack of control over the pore structure, which plays an essential role in facilitating sodium ion diffusion and accommodating volume changes during charge-discharge cycling. Summary of the invention

[0005] On one hand, hard carbon is characterized by a molecular sieve-type closed-pore structure that provides a surface and an internal space, and the structure also has a window for receiving sodium during charging, where sodium ions pass through the window and adsorb on the surface after charging, occupying the internal space.

[0006] On the other hand, the present invention discloses a method for preparing hard carbon. The method includes a two-step heat treatment (calcination) of a biomass mixture under specific conditions to achieve the ideal physical and chemical properties of the hard carbon product. The hard carbon with a molecular sieve type closed-pore structure is formed by the following method: calcining a biomass mixture with 70-90% cellulose, 9-20% hemicellulose and 1-10% lignin at 300-600°C to generate a pre-carbonized precursor; washing the pre-carbonized precursor with an alkaline solution and adjusting the pH value to 6.0-8.0; re-calcining the pre-carbonized precursor at 900-1400°C to generate a molecular sieve type closed-pore hard carbon.

[0007] In another aspect, an anode of a sodium ion battery includes a hard carbon material having a molecular sieve type closed pore structure.

[0008] In yet another aspect, a sodium ion battery includes a cathode; an electrolyte coupled to the cathode; and an anode coupled to the electrolyte, the anode having a plurality of molecular sieve-type closed-pore structures.

[0009] The implementation of the above aspects may include one or more of the following aspects. The biomass mixture may be an organic material rich in carbon. The biomass mixture is used as a precursor and undergoes a heat treatment process or calcination. The calcination step may thermally decompose the organic components of the biomass to produce a carbon structure. The calcination process is carried out in an inert gas to prevent oxidation of the carbonaceous material. The precursor is subjected to a temperature of 300-600°C. The temperature is increased at a rate of 2-10°C / min in an inert gas. This treatment process results in preliminary decomposition and carbonization of the biomass. Subsequently, the material is washed with an alkaline solution having a concentration of 0.05-1.0 mol / L to clean and activate the carbon surface. The second heat treatment extends to a high temperature of 900-1400°C. In an inert gas environment, the heating rate is 2-10°C / minute. In this re-calcination step, as the residual volatile substances are eliminated, the hard carbon structure is further developed, thereby increasing the porosity of the hard carbon material. The resulting hard carbon materials have optimized structures for the reversible insertion and extraction of Na ions, leading to high-performance SIBs.

[0010] The advantages of the material include one or more of the following. The method utilizes the inherent structure of biomass composed of cellulose, hemicellulose and lignin to form a hard carbon precursor with an ideal pore framework after calcination. By optimizing the calcination temperature and adopting post-treatment cleaning and re-calcination steps, the hard carbon material produced has a molecular sieve-type closed-pore structure, mainly with a target pore size distribution. This structure not only facilitates the rapid transport of ions, but also provides structural integrity and enhances the cycle stability of sodium-ion batteries. Given the natural abundance and renewability of biomass, the method uses biomass as a starting material, which is sustainable and cost-effective. The method can recycle agricultural waste, thereby promoting a more environmentally friendly production process while also solving waste management issues. The biomass mixture used in the disclosed method comes from agricultural waste, providing a rich renewable raw material for the production of hard carbon anode materials for sodium-ion batteries. By utilizing agricultural waste, the present method not only provides a sustainable battery manufacturing method, but also helps to manage and reduce agricultural waste, achieve a closed loop of the agricultural life cycle, and promote environmentally friendly practices.

[0011] Another advantage is that an optimized structure for sodium storage can be created, thereby developing sodium-ion batteries with higher capacity, rate performance and cycle stability. Therefore, this method has made significant progress in the design and synthesis of anode materials for next-generation energy storage technologies. The hard carbon produced by carefully controlled biomass calcination and chemical treatment processes has a molecular sieve-like closed-pore structure, which is very suitable as an anode material for sodium-ion batteries. The study found that this structure is very conducive to improving the electrochemical performance of the material, especially in Na + Kinetic aspects of ion insertion and extraction.

[0012] Another advantage of this method is that it can produce hard carbon with a molecular sieve-type closed-pore structure. Hard carbon materials have high surface area, appropriate pore distribution and conductivity, which are key characteristics for batteries to achieve fast charge and discharge rates and high energy density. These characteristics make molecular sieve-type closed-pore hard carbon a typical candidate material for advanced energy storage applications, thereby meeting the growing demand for renewable energy solutions and the transition to more sustainable energy storage technologies. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 TEM images of the hard carbon of the present invention and the sodium layer dispersion after charging are shown.

[0014] Figure 2 Exemplary XRD patterns of three hard carbon samples prepared using the method of the present invention are shown.

[0015] Figure 3 Exemplary Raman spectra of three hard carbon samples prepared using the method of the present invention are shown.

[0016] Figure 4 Exemplary TEM images of three hard carbon samples prepared using the method of the present invention are shown.

[0017] Figure 5 An example SIB performance curve is shown. DETAILED DESCRIPTION

[0018] The present disclosure relates to hard carbon characterized by a molecular sieve-type closed-pore structure and a method for preparing the hard carbon, the hard carbon being derived from a biomass mixture for use in sodium ion batteries. The method optimizes the pore structure within the hard carbon to enhance Na + ions, thereby increasing the storage capacity and efficiency of the battery.

[0019] In order to obtain the desired hard carbon structure, suitable carbon-rich biomass needs to be selected and prepared to ensure high carbon yield during processing. To prepare the biomass mixture, agricultural residues, which are considered to be by-products or wastes of agricultural activities, need to be collected. These residues may include but are not limited to plant stems, leaves, shells, husks and other cellulose-rich organic matter. These materials are usually subjected to preliminary treatments such as drying and grinding to achieve consistent particle size and homogenization, thereby achieving uniform calcination and chemical reaction.

[0020] Biomass undergoes a series of thermal and chemical treatments to transform into hard carbon, whose properties are favorable for storing energy in sodium-ion batteries. In one example, the biomass mixture includes cellulose, hemicellulose, and lignin in proportions that are favorable for efficient conversion to hard carbon. Specifically, cellulose is present at 70% to 90% and is the main carbon source. Hemicellulose, a structural polysaccharide found in plant cell walls, is similar to cellulose and is present at 9% to 20%. Lignin, an organic polymer that provides structural support to vascular plants and certain algae, accounts for 1%-10% of the mixture. This specific composition ensures that the necessary characteristics for hard carbon formation are met and that the resulting material has the properties required for electrochemical applications.

[0021] The biomass mixture contains 70-90% cellulose, 9-20% hemicellulose and 1-10% lignin. The biomass mixture is initially calcined at 300-600°C to obtain a precursor characterized in that cellulose is a carbon chain, hemicellulose is a short carbon chain and a pore structure, and lignin / other substances provide a pore structure. The precursor is then washed in an alkali with a concentration of 0.05-1.0 mol / L and then neutralized to a pH value of 6.0-8.0.

[0022] Then, a second calcination is carried out at 900-1400°C to produce the desired molecular sieve type closed-pore hard carbon. The obtained hard carbon is suitable for use as an anode material for sodium ion batteries.

[0023] After obtaining the biomass mixture, the process will calcine the mixture at a temperature ranging from 300°C to 600°C. The calcination process will cause thermal decomposition of the organic components in the biomass, promoting the conversion of the biomaterial into a pre-carbonized state. This precursor state is an intermediate step in the synthesis of hard carbon. During this process, the biomass undergoes a great deal of chemical changes due to the heat, but does not reach the stage of fully forming hard carbon.

[0024] After calcination, the pre-carbonized precursor generated from the biomass mixture is washed. Washing is performed using an alkaline solution to neutralize any residual acidic compounds that may be present in the pre-carbonized precursor and to produce a closed-pore structure. This process purifies the precursor and optimizes its chemical environment for subsequent conversion into hard carbon.

[0025] Alkali treatment can effectively embed sodium ions (Na + ). When the precursor material is treated with alkali, a series of chemical reactions occur that change the carbon structure to form carbon chains of different lengths. This improves the performance of sodium-ion batteries using hard carbon.

[0026] Taking NaOH as an example, adding NaOH to the carbonaceous precursor will cause a redox reaction, carbon (C) is oxidized, and the metal sodium (Na) and sodium carbonate (Na 2 CO3 ) and hydrogen (H 2 ) formation. This reaction promotes the activation of the carbon surface, thereby increasing the porosity and surface area, which is beneficial to Na + Diffusion and electrochemical activity of ions.

[0027] The subsequent reaction of the sodium metal with water (if present) produces additional NaOH and releases hydrogen. This step further affects the pore structure, creating an optimal environment that favors Na + Insertion and removal of ions during the charge and discharge cycles of a battery.

[0028] Through these reactions, the alkaline treatment modifies the biomass-derived precursor into a hard carbon form with a molecular sieve structure that can accommodate Na + ions, improving the cycling stability and energy capacity of sodium-ion batteries. This material is very suitable for use as an anode in energy storage systems, especially because of its high surface area, ideal pore size distribution, and functional groups generated during the alkaline activation process.

[0029] The action of the alkaline solution helps remove organic impurities as well as etches the carbon framework, thereby enlarging or forming pores required for ion transport. The choice of base depends on the desired chemical affinity and the specific characteristics of the precursors used.

[0030] The choice of alkaline solution is not limited to sodium hydroxide (NaOH), but other suitable solutions can also be selected, such as potassium hydroxide (KOH), lithium hydroxide (LiOH) and ammonia (NH 4 OH). Each alkaline solution has unique properties that affect the activation and pore development process of the precursor material, thus affecting the structure and properties of the final hard carbon product. NaOH is effective in enhancing the pore structure and increasing the accessibility of sodium ions, while KOH is known for its ability to produce larger pore volumes, and LiOH and NH 4 OH may produce different pore development dynamics due to different ion radii.

[0031] Cleaning not only cleans the precursor, but also helps the chemical activation of the carbon structure. After the pre-carbonized precursor is fully cleaned, it is heated in nitrogen (N 2 ) and argon (Ar) in an inert atmosphere at a controlled heating rate to eventually reach a target high temperature to form the desired hard carbon structure.

[0032] Increasing the temperature to 900-1400°C promotes the conversion of the activated precursor into its final form of hard carbon. It is at this stage that the unique pore structure is fixed and the material obtains the high surface area and porosity required for the effective embedding of sodium ions. This material composed of closed-pore hard carbon with pores less than 10nm is very suitable for use as an anode material for sodium-ion batteries because it provides an optimal ion transport path, thereby improving the battery's performance in terms of energy density, service life and charging rate. The molecular sieve structure formation process produces particles of a specific size range, ensuring the consistency of the material. The molecular sieve structure formation process can also separate closed-pore hard carbon particles with ideal pore size, thereby ensuring efficient Na during battery operation. + Ion insertion and extraction.

[0033] The second calcination is preferably carried out in nitrogen (N 2 The process is carried out in an inert gas such as argon (Ar) to prevent unwanted oxidation of the carbon material. The controlled processing environment and specific temperature regulation ensure that the formed hard carbon has an ideal pore distribution and integrity, thereby ensuring the consistency of electrochemical performance when used in sodium-ion batteries.

[0034] The present method of preparing powdered hard carbon and calcining it sequentially facilitates batch synthesis, thereby enabling large-scale production of anode materials. This scalability is an important consideration for the widespread adoption of sodium-ion battery technology in a variety of applications ranging from portable electronics to grid-scale energy storage systems. In addition, the use of biomass as a starting material makes full use of renewable resources, thus contributing to the sustainability of the entire production process.

[0035] The temperature of the second calcination is significantly higher than that of the initial calcination and is adjusted to a range of 900°C to 1400°C. The increase in temperature during the second calcination promotes the complete carbonization of the precursor material to form hard carbon. High temperature treatment promotes the evolution of non-carbon atoms and helps to form a graphite-like structure, which is necessary to achieve ideal conductivity and crystallinity. It is at this stage that the ideal molecular sieve closed-pore structure is formed. When hard carbon is used as an anode material, these closed pores are crucial to its efficacy because they can regulate the interaction between the hard carbon structure and sodium ions during the battery charge and discharge cycle. Hard carbon with such fine micropores exhibits better electrochemical performance when subsequently integrated into sodium-ion batteries, with advantages in energy storage capacity, cycle life and rate performance.

[0036] In this patent, the method ensures the formation of a hard carbon structure with specific molecular sieve closed-pore characteristics, making it suitable for use as an anode material for sodium-ion batteries. + ) is larger than lithium (Li + ). Therefore, Na + Cannot be embedded in graphite anode. Due to the short disordered structure, Na+ Ions can: i) be adsorbed on the hard carbon surface; ii) be embedded in the hard carbon layer; iii) be accumulated in the closed-pore structure. + The increase in the amount of carbon has a positive effect on the electrochemical performance of SIBs. Figure 1 As shown in Figure 2, the sodium layer dispersion after charging is also as shown in Figure 2. Figure 1 As shown, Na + (1) adsorbed on the surface, (2) embedded in the carbon layer, and (3) aggregated in the pores. The resulting structure has high Coulombic efficiency and high specific capacity, thereby extending the battery life. Molecular sieve hard carbon is characterized by uniform pore distribution, which is related to the Na + The efficiency of ion embedding is directly related to the efficiency of ion embedding. This efficiency is particularly important because uniform and optimal pore size less than 10nm can improve ion conductivity and charge-discharge cycle stability, thereby improving the energy storage and life of the battery.

[0037] Figure 1 The transmission electron microscope (TEM) image shows the pore structure with a pore size of less than 10nm that forms the molecular sieve structure. The image obtained reveals the intricate details of the material's microstructure and provides direct evidence of the successful production of molecular sieve-type closed-cell hard carbon particles with uniform pore size. In this image, we can clearly see the uniformity and distribution of pores inside the carbon matrix, which is a characteristic of the molecular sieve-type structure.

[0038] Closed-pore hard carbon structures are an indispensable component of sodium-ion battery anode materials. The closed pores provide discrete locations for the embedding and storage of sodium ions in hard carbon materials. + The ions are confined in these pores, providing a stable environment that reduces the likelihood of harmful reactions with the electrolyte or other components of the battery, helping to improve the efficiency of the charge and discharge cycles. The resulting molecular sieve-type structure ensures that most of the pores are less than 10nm in size. As a result, most of the pores in the hard carbon material shown in the figure are within this optimal size range, which is beneficial for the Na+ transfer during battery operation. + The kinetics of insertion and extraction of ions are particularly favorable. In addition, the figure also depicts the results of chemical and thermal treatments, including the chemical reaction NaOH + C → Na + Na produced by the use of NaOH 2 CO 3 +H 2 , and Na+H 2 O→NaOH. These treatments help to increase the porosity and electrochemically active surface area of ​​the carbon.

[0039] In the case of Na +As one aspect of ion intercalation, molecular sieve-type closed-pore hard carbons can obviously improve the electrochemical performance of sodium-ion batteries. The molecular sieve-type structure is designed to selectively allow Na + Ion insertion. Controlled insertion of Na + Ions are inserted into finely tuned pore sizes (less than 10 nm in one example) to ensure efficient use of the available electrochemical surface within the molecular sieve-type structure and maximize charge storage capacity.

[0040] Once embedded, Na + The ions are then located in the pores of the molecular sieve-type closed-pore structure, providing a stable and efficient pathway for ion transfer during battery operation. + The molecular sieve-type closed-pore structure of the ions significantly improves performance when used as anode materials for sodium-ion batteries, showing excellent charge capacity and enhanced cycling stability.

[0041] The preparation of hard carbon begins with the selection of a suitable biomass mixture. This mixture comes from carbonaceous organic matter that can be converted into solid carbon through thermal decomposition. To ensure the quality and consistency of the pore structure, the biomass needs to undergo a calcination process. The initial calcination temperature is about 300-600°C. During the calcination process, the volatile components in the biomass are driven out, leaving a carbon-rich residue.

[0042] After the initial calcination, the resulting carbonaceous material is mixed with an alkaline solution. The chemical reactions that occur at this stage not only activate the carbon material, but also play an important role in the pore development process. Specifically, the interaction with the base promotes the opening of pores within the carbon structure, preparing the material for subsequent processing.

[0043] During the washing step, impurities that may have been introduced during the calcination process or that are inherent in the biomass precursor are removed, which would otherwise negatively affect the electrochemical performance of the hard carbon when it is used as an anode material for sodium-ion batteries.

[0044] After washing and further cleaning, the carbon material is calcined a second time, this time at a much higher temperature of 900-1400°C. It is during this re-calcination that the carbon material solidifies into hard carbon. At the same time, this treatment also effectively creates a pore structure, forming closed pores with a median distribution of pores less than 10nm.

[0045] After high temperature treatment, the hard carbon produces a molecular sieve-type structure, which is the role of this process to give the material the desired pore structure. This is a key step to ensure that the final product has a consistent, uniform molecular sieve-type closed-pore structure, thereby promoting the target Na + Ion transport kinetics.

[0046] Initially, the biomass mixture, as a precursor for closed-cell hard carbon, is calcined at a reference temperature of 300-600°C. This stage eliminates volatile compounds and initiates the carbonization of the biomass. The precursor is then treated with an alkali, which results in the initial formation of the desired porous carbon structure. To further refine the carbon structure, a re-calcination at a higher reference temperature of 900-1400°C is required. This step enhances the energy storage properties of the carbon matrix, namely electrical conductivity and ion accessibility.

[0047] The heat treatment step at 900-1400°C removes any remaining non-carbon elements and promotes Na + The production of graphitic structures for ion storage. In addition, this rigorous high temperature helps achieve the ideal graphitization and porous structure, which are necessary features for efficient ion transport and intercalation. The use of inert gas (usually nitrogen) during the re-calcination process prevents oxidation of the carbonaceous material and facilitates the formation of the porous network required for the target application.

[0048] During the pre-carbonization stage, the temperature should be kept below 600°C to prevent excessive ash formation, which would reduce the quality of the final carbon product. Conversely, the temperature should be kept above 300°C to ensure sufficient thermal decomposition of the biomass components. This controlled thermal treatment is required to decompose the lignocellulosic structure and other organic compounds in the biomass mixture, thereby producing a pre-carbonized material with a porous matrix necessary for subsequent activation and formation of the final hard carbon structure.

[0049] After the pre-carbonization step, the resulting semi-carbonized biomass mixture is immersed in an alkali solution to initiate the chemical activation process. The alkali not only removes residual impurities from the carbonized material, but also creates additional porosity by etching the carbon skeleton. The reaction between the alkali and the carbon element forms carbonates and hydrogen, which further affect the material's textural properties.

[0050] The activated material will then enter the second stage of carbonization (called re-calcination), which is heated to a temperature of about 900-1400°C. At this stage, the porous carbon structure that has been formed will be transformed into a densely packed layer similar to graphene, that is, hard carbon. This re-calcination at a higher temperature removes the remaining non-carbon elements, thereby purifying the carbonaceous material and enhancing the conductivity required for the battery anode.

[0051] The process can achieve a narrow pore size distribution, in one case where the pore size is mainly less than 10nm. This small pore size is conducive to the insertion and extraction of sodium ions during the battery charge and discharge cycle. The molecular sieve structure is produced through processing to achieve this reasonable closed-pore distribution by taking advantage of the size difference between the required porosity and the larger, unusable pore structure.

[0052] Finally, this molecular sieve type microscopic closed-pore hard carbon is loaded into a sodium-ion battery. This hard carbon serves as an anode in which sodium ions are embedded. The dense pore structure not only enables efficient sodium ion transport, but also improves the overall energy density and charge and discharge rate of the battery. This innovative approach combines sustainable raw materials with precise thermal and chemical processing, ultimately forming an advanced energy storage solution that meets the growing demand for renewable and high-performance battery technology.

[0053] If alkali washing is not performed, a mixture of soft carbon and hard carbon will be produced. In addition, when the re-calcination temperature is higher than 1400°C, glassy carbon will be produced.

[0054] During the calcination process and the subsequent re-calcination step, most of these trace impurities are reduced or eliminated. High temperatures lead to the volatilization and decomposition of many organic compounds, and inorganic substances may be transformed or oxidized to form ash. Ash can be removed from the final product by various purification methods such as washing, filtering or acid treatment.

[0055] After the initial heat treatment, the precursor undergoes a chemical reaction with a base, which has a dual role: it helps activate the carbon structure, promoting the formation of porosity; and it also reacts with certain impurities to form soluble salts that can be washed away, thus aiding the purification process.

[0056] One or more trace impurities are often present in natural sources of biomass, and these impurities may include, but are not limited to, potassium ions (K + ), calcium ions (Ca 2+ ) and magnesium ions (Mg 2+ ). When hard carbon is used as anode material for sodium-ion batteries, the presence of these impurities may affect its electrochemical properties.

[0057] Potassium ion (K + ) may be a result of biomass composition or may be a residue of processing chemicals used during the extraction and purification of carbon materials. These ions may occupy active sites within the carbon lattice or reside in micropores, affecting Na + The movement of ions affects the storage capacity.

[0058] Likewise, calcium ions (Ca 2+ ) and magnesium ions (Mg 2+ ) are also incorporated into the carbon structure. These multivalent impurities may affect the conductivity and cause changes in the pore structure due to their large ionic size and possible interaction with the carbon matrix.

[0059] Although these impurities are trace and make up only a small fraction of the overall hard carbon composition, they can affect the overall performance of the material. Therefore, during the manufacturing process, steps can be taken to reduce the concentration of these impurities or to exploit their presence to optimize electrochemical performance.

[0060] In addition, strategies to mitigate the impact of these trace impurities on Na-ion battery performance may include additional purification processes, post-treatment improvements, or incorporation during a controlled calcination stage to change their state, distribution, or interaction with Na + Interaction of ions.

[0061] In one example, impurity removal is achieved by first washing the biomass mixture with an acidic solution. The pH of this acidic solution is strictly controlled between 3 and 6, ensuring that it is acidic enough to dissolve and remove various impurities present in the biomass, such as minerals, inorganic salts, and other non-carbonaceous components. The selected pH range is critical to effectively remove impurities from the biomass without causing excessive degradation of the organic matter required for the subsequent carbonization process.

[0062] In another embodiment, the cleaning process lasts from 2 to 10 hours, depending on the type and amount of impurities in the biomass. This duration is selected to optimize the acid cleaning effect while minimizing the risk of damaging the integrity of the carbon precursor in the biomass. During this period, the biomass mixture is completely immersed in the acid solution, which allows for sufficient interaction between the acid and the impurities, thereby enhancing the overall cleaning effect.

[0063] After acid washing, the biomass mixture is subjected to a second water wash. The purpose of the water wash is to remove the acid or acids used in the impurity removal process. This step must be performed carefully to ensure that all traces of the acidic solution in the biomass mixture are removed. The presence of residual acid may interfere with downstream processes such as calcination and negatively affect the properties of the prepared hard carbon material.

[0064] The water used for washing is usually neutral or close to neutral pH to counteract the acidity from the previous washing step. The biomass is washed thoroughly to ensure that no acidic material remains. The water wash not only neutralizes the biomass, but also further removes any soluble impurities that have been loosened but not completely dissolved by the acid wash.

[0065] After the washing step, the biomass mixture is dried to remove the added water. The drying step prepares the biomass for subsequent high-temperature treatments such as calcination and re-calcination at temperatures of 300-600°C and 900-1400°C, respectively, to convert the biomass into a structured hard carbon material suitable for use in sodium-ion batteries.

[0066] Through these cleaning processes, the biomass mixture is conditioned into a high-purity precursor that is conducive to the production of high-quality hard carbon materials characterized by a molecular sieve-type closed-pore microstructure that is ideally suited to accommodate Na during the operation of sodium-ion batteries. + ion.

[0067] Another embodiment is to use an acidic solution to treat and optimize the porosity and chemical properties of the material. The acidic solution is composed of one or more acids selected from nitric acid (HNO 3 ), hydrochloric acid (HCl), acetic acid (CH 3 COOH), sulfuric acid (H 2 SO 4 ) and phosphoric acid (H 3 PO 4 ). These acidic solutions serve several purposes in the treatment of the biomass precursor and the resulting hard carbon. First, it acts as a cleaning agent, removing impurities and potentially catalyzing reactions that would hamper the performance of the hard carbon as an electrode material. Typically, the use of an acidic solution involves an acid wash step, where the biomass mixture is immersed in an acidic medium. The choice of acid or acid combination depends on the desired chemical reactivity and the nature of the biomass used. Reaction with nitric acid generally helps to introduce nitrogen doping sites into the carbon matrix, which has the potential to enhance electronic conductivity and provide active sites for sodium ion storage. Hydrochloric acid treatment is known to be beneficial in removing metallic impurities and helps to open up the carbon pore structure. Acetic acid, due to its relatively mild acidity, can be used to modify the surface chemistry without excessively etching the carbon framework. Finally, sulfuric acid, known for its strong oxidizing ability, can be used to embed sulfonic acid groups into the carbon surface, thereby increasing the hydrophilicity and possible ionic conductivity of the material. In the process of preparing hard carbon, the biomass mixture is subjected to these acids under controlled conditions, with concentrations, temperatures, and length of contact time varying depending on the desired properties of the final product. After the acid treatment, the mixture is thoroughly washed to remove residual acid and byproducts. This is followed by a calcination step, which helps to form a stable carbonaceous structure, usually resulting in a molecular sieve-type closed-pore structure described later, which has a specific pore size that is conducive to the efficient insertion and extraction of sodium ions during battery operation. The molecular sieve-type closed-pore structure obtained by this method can optimize the role of the sodium-ion battery anode by selectively capturing hard carbon particles with a desired pore size. The alkaline treatment, calcination, and re-calcination process ensure that the carbon material has appropriate conductivity and stability to effectively circulate sodium ions. The molecular sieve-type closed-pore structure and the embedded Na + The combination of ions forms a robust and efficient sodium-ion battery electrode with the potential for high energy density, long cycle life, and cost-effectiveness due to the use of abundant starting materials and a scalable manufacturing process.

[0068] Furthermore, the method supports sustainable production practices since biomass, a renewable resource, is used as the carbon source. The transformation of this raw material into advanced energy storage solutions is particularly important considering the current shift towards renewable energy systems and the need for compatible energy storage technologies.

[0069] The pre-carbonized precursor may be subjected to a washing step with water. The washing step removes any loose dust and particulate matter that was not chemically bonded to the precursor material during the pre-carbonization process. The process may include agitation or sonication to enhance the washing action, followed by a filtration or decantation step to separate the solid carbonaceous material from the particles suspended in the washing water.

[0070] After the pre-carbonized precursor is thoroughly cleaned, it is then cleaned with an alkaline solution. The alkaline treatment includes the use of KOH, NaOH, LiOH, and NH 4 OH solutions, which react with the carbonaceous material. This step is necessary as it promotes the opening of pores in the pre-carbonized structure, thereby promoting the development of a network of accessible channels and cavities in the carbon matrix. Alkaline cleaning not only helps functionalize the carbon surface and increase its reactivity, but also plays an important role in pore development.

[0071] The alkaline solution washing is carried out under controlled conditions to ensure that the interaction between the alkali and the pre-carbonized precursor is sufficient to penetrate into the pores without destroying the overall structure of the carbon matrix. Parameters such as the concentration of the alkaline solution and the contact time between the alkali and the precursor are carefully optimized to produce the desired porous structure and distribution in the hard carbon produced in the subsequent steps.

[0072] After the alkaline treatment, the precursor can undergo an additional washing step to remove excess alkali and salts formed by chemical reactions during the alkaline treatment. When used as an anode material in sodium-ion batteries, the hard carbon has an optimized structure that is conducive to Na + ion intercalation and storage, so hard carbon is expected to show excellent performance.

[0073] In the production of hard carbon composites, a biomass mixture is used as the primary source of carbon. This biomass mixture can be any kind of carbon-rich organic material that can serve as a precursor in the pyrolysis process. The choice of biomass can affect the characteristics of the final hard carbon product.

[0074] The precursor is calcined in a nitrogen atmosphere, gradually increasing the temperature to 300-600°C at a rate of 2-10°C / min and maintaining this temperature for 2-10 hours. This temperature is carefully selected to achieve initial carbonization while maintaining the structural integrity of the biomass.

[0075] The electrochemical properties of hard carbon are further improved by adjusting the sodium ion embedding capacity. This is done by adjusting the pore size distribution to ensure that the pore size is suitable for Na + or Li + Intercalation of ions. During battery charging, these ions are embedded in the pores of the hard carbon, and during discharge, the ions are extracted, allowing an electric current to flow through the battery. The achieved uniformity in pore size makes the intercalation and extraction processes more consistent and efficient, resulting in a more stable battery with a higher energy capacity.

[0076] The preparation of hard carbon composites requires a delicate process of calcination, washing, re-calcination and screening to achieve the ideal electrochemical properties for use in energy storage systems. The properties of hard carbon, such as a specific pore structure suitable for ion embedding, provide better anode materials for next-generation lithium-ion and sodium-ion batteries. This improved performance is due to the controlled microstructure obtained from sustainable biomass sources, which improves the ion storage capacity and the overall efficiency of the battery.

[0077] The method also includes a washing step for the carbon powder precursor. After an initial calcination step at a temperature of 300-600°C, the carbon powder precursor obtained from the biomass mixture is purified by a washing step. The water washing ensures the removal of any soluble impurities, non-carbon elements and ash that may be present in the precursor material. The water washing not only helps to purify the carbonized product, but also helps to expose and expand the pore structure, which is crucial for the subsequent alkali treatment.

[0078] After washing with water, the clean porous carbon powder is treated with an alkali as described above. The alkaline environment forms a more accessible channel network in the carbon matrix. This chemical activation process promotes an increase in specific surface area, which is exactly what is needed to improve electrochemical performance.

[0079] The cleaned activated carbon powder is then further heat treated by subjecting it to temperatures between 900-1400°C under inert gas. This high temperature treatment, also known as re-calcination, is intended to improve the structural integrity of the hard carbon. This step helps improve the electrical conductivity of the final product.

[0080] The alkali treatment is performed by immersing the carbon powder in an alkali solution with a concentration ranging from 0.05 to 1.0 mol / L. The exact alkali concentration is selected based on the desired porous structure and the electrochemical performance required for a specific application. The immersion time is kept between 2 and 10 hours, and this time period is chosen to allow for sufficient interaction between the alkali and the carbon powder. During this period, the alkali acts on the carbon material, etching specific sites and expanding the interlayer space within the carbon domains. This etching not only increases the pore volume, but also improves the patency of the pore structure, making it more accessible to the embedding of sodium ions.

[0081] As the interlayer spacing increases, the ion diffusion kinetics of the pore structure improves, which is directly related to the improvement of battery performance. Strategic manipulation of the interlayer spacing and pore size aims to achieve a delicate balance between structural stability and ion transport efficiency. Therefore, carbon structures with increased interlayer spacing have considerable advantages in energy storage in sodium-ion battery systems.

[0082] After the alkaline treatment, the carbon material is thoroughly washed to remove any residual alkaline that may be attached to the surface. This washing step ensures that the integrity of the newly formed pore structure is not affected by residual treatment reagents. The carbon powder is then dried to remove any moisture that could affect the interlayer spacing measurements and the performance of the material during subsequent battery assembly and testing.

[0083] By effectively controlling the alkaline treatment, the customized porosity of the carbon material can be achieved, facilitating the development of high-performance hard carbon anodes required for advanced sodium-ion batteries. Compared with traditional hard carbon materials, this innovative synthesis method significantly improves the energy density, cycle life and charging rate of next-generation sodium-ion batteries.

[0084] The treated carbon powder obtained after calcination and chemical activation is washed. The washing method is to wash the carbon powder with water until the pH of the mixture is neutral, ranging from 6.0 to 8.0. The purpose of this washing step is to remove any residual chemical reagents, especially unreacted bases and by-products. Achieving a neutral pH is crucial because it indicates that the excess base has been completely washed away, leaving behind a pure carbon material without contaminants that may adversely affect battery performance. This neutral pH also indicates stable surface chemistry, which is necessary for the hard carbon to maintain stable electrochemical performance when used as an anode material in sodium-ion batteries. The resulting clean and pH-neutral carbon powder has an ideal microstructure that promotes efficient insertion and extraction of sodium ions during battery charge and discharge cycles. This process step is crucial to ensure that the physical and electrochemical properties of the hard carbon are maintained at optimal levels for subsequent use in energy storage devices. After the washing procedure, the washed carbon powder is dried at an appropriate temperature to remove any residual moisture that may affect the material's conductivity and ion transport properties. Once the drying process is complete, the carbon material can be further characterized or directly incorporated into a battery cell as an anode component for performance evaluation in a sodium-ion battery system with respect to capacity, cycle life, and overall efficiency.

[0085] The production process of hard carbon for sodium-ion batteries includes a step of cleaning the pre-carbonized precursor. The biomass mixture is preliminarily calcined under inert gas at a temperature of 300-600°C for 2-10 hours. After the pre-carbonized precursor is formed, it needs to be thoroughly cleaned. An alkaline solution is used for cleaning. The concentration of the alkaline solution is strictly controlled within a specified range, that is, between 0.05 and 1.0 mol / L. The purpose of alkaline cleaning is to effectively remove impurities and any remaining volatile substances that may be present in the pre-carbonized precursor. This step is very critical because it affects the structural characteristics of the resulting hard carbon.

[0086] The duration of the alkaline solution cleaning is also a variable parameter and can vary from 2 to 10 hours. The choice of cleaning time depends on the desired pore structure and the chemical purity of the hard carbon. Longer cleaning times may result in a more activated carbon structure, while shorter cleaning times may be sufficient for certain precursor compositions and desired pore distributions.

[0087] After the alkaline solution wash, the pre-carbonized precursor undergoes another water wash. The water wash continues until the pH of the solution is close to neutral (pH between 6.0 and 8.0). The water wash ensures the removal of any alkali residues from the previous processing steps. It also helps neutralize the carbon material, making it safe for handling and further processing. A thorough water wash step is required to prevent any undesirable chemical reactions during subsequent heat treatment and to ensure the purity of the hard carbon.

[0088] After being thoroughly cleaned and washed with water, the pretreated precursor is calcined at a high temperature of 900-1400°C, which helps to form high-quality hard carbon. This hard carbon has an optimized closed-pore structure and is very suitable for the embedding of sodium ions when used as an anode material for sodium-ion batteries. Through this systematic and precise treatment process, the precursor is transformed into an efficient material with great potential in energy storage applications. The resulting hard carbon anode material can improve the performance and life of sodium-ion batteries, thereby helping to provide more sustainable and reliable energy storage solutions.

[0089] Figure 2 Exemplary XRD patterns of three hard carbon samples prepared using the method of the present invention are shown. An amorphous structure is obtained. There are no peaks belonging to graphite, indicating that the hard carbon synthesis is successful. The peak position is between 23.5 and 23.9°, indicating that the interlayer spacing is wider than that of graphite. Figure 2The XRD pattern in shows two broad peaks, which are characteristic of hard carbon. The absence of graphite peaks indicates that the sample is highly amorphous. The first peak is centered at approximately 23.5 to 23.9° due to the (002) plane of hard carbon. The calculated carbon interlayer spacings are 0.3414, 0.3404, and 0.3411 nm, respectively, indicating that the carbon interlayer spacing is wider compared to graphite. The second peak is centered at approximately 44.0° due to the (101) plane of hard carbon. The intensity of the (002) peak is generally greater than that of the (101) peak.

[0090] Figure 3 The Raman spectra of three hard carbon samples prepared using the method of the present invention are shown in Figure 1. The Raman spectra of the three hard carbon examples show two main features: -1 The width of the D belt is about 1580cm -1 The sharp G band at the center of the carbon structure is due to the presence of disorder and defects, while the G band is due to the sp 2 In-plane stretching vibration of bonded carbon atoms. The intensity ratio ID / IG of the D band and the G band is a measure of the degree of disorder of the carbon structure. The higher the ID / IG ratio, the higher the degree of disorder. The ID / IG ratios of Example 1, Example 2, and Example 3 are 1.2549, 1.2241, and 1.2424, respectively. The ratio is continuously above 1.000, confirming the disordered short-chain structure of hard carbon. It is known that the degree of disorder of the carbon structure will affect the performance of the hard carbon electrode. Hard carbon electrodes with higher disorder tend to have higher specific capacity and better rate performance.

[0091] Figure 4 Exemplary TEM images of three hard carbon samples prepared using the method of the present invention are shown. The method produces a molecular sieve-type closed-pore structure, which is depicted by imaging techniques such as TEM, thereby providing visual confirmation of the nanoscale pore size distribution within the hard carbon. The resulting hard carbon material with a molecular sieve-type closed-pore structure supports Na + Rapid intercalation of ions. This property is very useful for efficient sodium-ion batteries, because reversible and rapid ion exchange is required between the anode and cathode during the charge and discharge cycles. Figure 4 It can be seen that the obtained hard carbon shows short and disordered carbon chains. The short chains build a closed-pore structure, increasing the interlayer spacing and Na + Space for embedding and storage.

[0092] Figure 1 The SIB anode in the present invention has closed pores required for efficient storage of sodium ions, which serve as a reservoir for Na +The main microstructure of the ions. The resulting closed-pore structure can prevent the formation of a solid electrolyte interphase (SEI) within the nanopores, which is beneficial to battery performance. In this case, pore size and distribution are necessary to improve reversible capacity and initial Coulombic efficiency (ICE), while an upper limit of pore diameter less than 10nm ensures the reversibility of the platform capacity.

[0093] SIB cathodes can use materials such as sodium metal oxides or phosphates. The electrolyte in these batteries is a sodium salt dissolved in an organic solvent, and the anode consists of hard carbon with a molecular sieve-type closed-pore structure, which helps prevent excessive electrolyte decomposition in the pores. Sodium ion storage in hard carbon anodes occurs through multiple mechanisms, including intercalation between carbon layers, adsorption on the surface, and pore filling.

[0094] This process has several associated performance advantages. Hard carbon anodes with optimized pore structures can achieve up to 300 mAh g in various implementations. -1 Platform capacity and 382mAh g -1 The molecular sieve-type closed-pore structure can significantly improve the initial Coulombic efficiency, with some designs reaching about 85%. In addition, the closed pores improve the capacity of the low-voltage platform and reduce electrolyte decomposition by minimizing the unwanted SEI formation within the pores. By carefully controlling the pore structure, microstructure and defects of the hard carbon anode, the researchers aim to further improve the electrochemical performance of SIBs, making them a viable and cost-effective alternative to lithium-ion batteries.

[0095] Various electrolytes can be used in SIBs. Organic liquid electrolytes made by dissolving sodium salts in organic solvents can be used. NaClO 4 Organic liquid electrolytes are widely used due to their good compatibility with common cathode materials. Solid electrolytes can also be used, including materials such as sodium super ion conductors (NASICON), which have high ionic conductivity and are non-flammable, making them safer than liquid electrolytes. During the charge and discharge cycle, the electrolyte acts as a medium for the movement of sodium ions between the cathode and the anode. It also participates in the formation of the solid electrolyte interface (SEI) on the anode and the cathodic electrolyte interphase (CEI) on the cathode, which is necessary for the electrochemical performance of the battery.

[0096] SIB can utilize a variety of biomass materials as a starting point, including but not limited to organic farm products and cotton. This raw material can be processed under controlled conditions, such as gradually increasing the temperature in an inert gas, followed by washing with an alkaline solution and additional heat treatment. This meticulous control of the production process ensures the development of hard carbon anodes that are well suited for next-generation energy storage systems.

[0097] The biomass mixture contains one or more trace impurities that are inherently present due to the nature of the biomass from which the mixture is derived. Trace impurities commonly associated with biomass may include, but are not limited to, inorganic salts, metals, and non-carbon organic compounds present in trace amounts. These impurities may come from soil, water, or air that comes in contact with the biomass during the biomass growth and harvesting stages. The present method is capable of producing molecular sieve-type closed-pore hard carbons that are particularly advantageous for use as anode materials in lithium-ion and sodium-ion batteries. The present method systematically uses a biomass mixture as a starting material, which provides an environmentally friendly and cost-effective raw material compared to fossil fuel-derived carbon sources. The biomass mixture is subjected to a calcination process at a temperature of 300-600°C to initiate carbonization of the biomass. This is followed by treatment with NaOH, in which a specific chemical reaction is carried out to activate the carbon structure and increase its porosity. The chemical reaction produces Na and Na 2 CO 3 , while releasing H 2 In addition, Na reacts with water to produce further NaOH. The hard carbon is then calcined to produce a molecular sieve structure. This step is critical because it ensures that the final product contains only particles with optimal pore sizes (specifically less than 10nm). The small size of these pores helps promote Na during battery operation. + The insertion and diffusion of ions, which is necessary for high efficiency and battery performance. This molecular sieve formation process not only selects the pore size, but also helps achieve a uniform distribution of pores, which contributes to the homogeneity of the final anode material.

[0098] The anode of the SIB includes a hard carbon material characterized by a molecular sieve-type closed-pore structure with a surface and an internal space, which also has a window structure for receiving sodium during charging, wherein the sodium ions pass through the window and adsorb on the surface and occupy the internal space after charging. The anode has a pore structure required for efficient sodium ion storage, as a means of accommodating Na +The main microstructure of ions. The closed pores have tight entrances, which produce a sieving effect and prevent the formation of a solid electrolyte interface film (SEI) inside the nanopores, which is beneficial to the battery performance. The pore size and distribution are necessary, and ultra-micropores can improve the reversible capacity and initial coulombic efficiency (ICE), while the upper limit of the pore diameter less than 10nm ensures the reversibility of the platform capacity. The closed-pore structure not only improves the reversible capacity, but also helps to improve the initial coulombic efficiency. For example, a carbon anode rich in closed pores can achieve a reversible capacity of 309.3mAh / g with an initial coulombic efficiency of 87.8%. The design of these closed pores is necessary for optimizing the storage of sodium because they provide a stable environment for sodium ions during the charge and discharge cycles, thereby improving the overall cycle stability and energy density of SIBs.

[0099] The sodium ion battery includes a cathode; an electrolyte coupled to the cathode; and the above-mentioned anode coupled to the electrolyte. The anode has a plurality of molecular sieve-type closed-pore structures having a surface and an internal space, and the structure also has windows for receiving sodium ions, wherein the sodium ions pass through the windows and are adsorbed on the surface and occupy the internal space after charging. The closed pores are characterized by their small entrance size, resulting in a molecular sieve structure. This design prevents the formation of a solid electrolyte interface (SEI) within the nanopores, which is a common problem of porous carbon because porous carbon has large surface area pores for the electrolyte to enter. Therefore, compared with traditional porous carbon materials, this molecular sieve-type hard carbon exhibits superior electrochemical performance. For example, porous carbon can only achieve a reversible capacity of 39 mAh / g, but molecular sieve-type hard carbon can achieve a higher capacity, such as 328 mAh / g at a current density of 50 mA / g.

[0100] This design has multiple performance advantages. Hard carbon anodes with optimized pore structure can achieve platform capacities up to 300 mAh g-1 and reversible capacities of 382 mAh g-1 in various implementations. The molecular sieve-type closed-pore structure can significantly improve the initial Coulombic efficiency, with some designs reaching up to 80.21%. In addition, the closed pores increase the capacity of the low-voltage platform and reduce electrolyte decomposition by minimizing the undesirable SEI formation within the pores. By controlling the pore structure, microstructure, and defects in hard carbon anodes, the electrochemical performance of sodium-ion batteries can become a viable and cost-effective alternative to lithium-ion batteries.

[0101] Figure 5 More battery data are shown, especially the capacity and ICE of Example 1, Example 2 and Example 3. The obtained hard carbon shows a high discharge capacity of more than 240 mAh / g and an ICE of more than 80%. The data are as follows:

[0102] The structure of hard carbon is as follows: short carbon chain; highly disordered structure; long interlayer spacing; and closed pore structure. Due to the short disordered structure, Na + Ions can be adsorbed on the hard carbon surface; embedded in the hard carbon layer; and aggregated in the closed-pore structure. + The amount of MgO increased and had a positive effect on the electrochemical performance of SIBs.

[0103] In one embodiment of the biomass mixture processing, the pre-carbonized precursor obtained after the first calcination step can be ground to produce a fine powder. Such grinding can ensure uniformity in particle size and morphology, as well as increase the surface area of ​​the precursor material. The increased surface area is critical to the performance of hard carbon as it can potentially enhance Na by providing more accessible active sites for electrochemical reactions. + ion intercalation capability. The grinding process is carried out using suitable grinding equipment known to those skilled in the art, such as a ball mill, jet mill or mortar and pestle, until the desired powder consistency is achieved. Care is taken to avoid contamination of the precursor material, as impurities can affect the electrochemical properties of the final hard carbon product. After grinding, the powdered pre-carbonized precursor, having a significantly reduced particle size, is directed to a second calcination step. As previously indicated, here the precursor undergoes a severe heat treatment at a temperature of about 1300°C. The high temperature transition helps to remove any residual inorganic matter and promotes the graphitization process. The product produced by the second calcination is a more crystalline hard carbon, which gives it better electrical conductivity and mechanical stability. In addition, the smaller particle size produced by the grinding step through the NaOH treatment allows the Na + ions can be more uniformly embedded in the molecular sieve structure of hard carbon. + The molecular sieve-type closed-pore structure of ions was demonstrated to have enhanced electrical properties and is suitable for use as anode materials in sodium-ion batteries. This structure effectively allows Na + The selective insertion of ions ensures that the battery operates efficiently and has optimal charging and discharging rates.

[0104] The prepared biomass mixture was calcined at 450°C, during which the organic matter in the biomass was thermally decomposed in an inert nitrogen atmosphere. The thermal treatment was carried out at a specific heating rate of 5°C / min and maintained for 3 hours, gradually transforming the biomass into a carbonized state while avoiding sudden thermal shocks, which could damage the structural integrity of the material.

[0105] Next, to increase porosity and activate the resulting carbon, the material was treated with an aqueous NaOH solution. This alkaline treatment reacts with the carbonized biomass as described by the chemical equation, where the NaOH interacts with the carbon to form sodium carbonate and hydrogen gas. This process also helps to enlarge the pore structure within the carbon matrix, thereby forming a network of channels suitable for ion transport.

[0106] After the NaOH treatment, the precursor was further heated under nitrogen gas to 1300°C. This re-calcination step stabilized the hard carbon by removing any remaining non-carbon species and aligning the carbon domains to enhance electrical conductivity and structural elasticity.

[0107] Sieving of hard carbon selectively removes particles based on pore size. It ensures that only particles with optimal pore size (specifically pore size less than 10nm) are used. These pores are ideal for accommodating Na + ions, thereby maximizing the charge storage capacity of the hard carbon.

[0108] Finally, the resulting embedded Na + The molecular sieve-like structure of the ions represents a material with a high density of accessible active sites, enabling reversible Na + "Through this approach, we have established a sustainable and cost-effective pathway to convert agricultural waste into a valuable ingredient for the growing energy storage market, an important step in the development of green technology solutions."

[0109] The resulting hard carbon has a dense, uniform pore structure of approximately 10 nm, providing a unique structure that maximizes the Na + The accessible surface area for ion embedding also helps form a stable and strong electrode material. This structure helps reduce strain during charge and discharge cycles, which can not only increase the overall capacity of the battery, but also improve its lifespan and cycle stability.

[0110] Taking into account the variation of biomass precursors and the differences in the subsequent re-calcination results, process parameters (such as temperature holding time and heating rate) can be optimized to obtain hard carbon with specific microstructural characteristics tailored to meet the intended electrochemical applications. Through this thermal treatment process, molecular sieve-type closed-pore hard carbon is achieved, which is subsequently integrated into the anode to provide excellent capacity retention and rate performance to meet the increasingly urgent energy storage requirements.

[0111] While particular embodiments and examples of the invention have been illustrated and described, numerous modifications are conceivable without departing significantly from the spirit of the invention, the scope of which is limited only by the scope of the appended claims.

Claims

1. A hard carbon with a molecular sieve type closed-pore structure, wherein the raw material for preparing the hard carbon is a biomass mixture, which contains 70-90% cellulose, 9-20% hemicellulose and 1-10% lignin, and the pore size of the molecular sieve type closed-pore structure is less than 10nm.

2. A method for preparing the hard carbon according to claim 1, comprising: 1) calcining the biomass mixture at 300-600° C. to produce a pre-carbonized precursor; 2) washing the pre-carbonized precursor with an alkaline solution and then adjusting the pH value to 6.0-8.0; and 3) calcining the pre-carbonized precursor at 900-1400° C. to produce molecular sieve type closed-cell hard carbon.

3. The method according to claim 2, wherein the calcining of the biomass mixture is carried out in an inert gas.

4. The method according to claim 2, wherein the temperature of calcining the biomass mixture is between 300-600°C. 5 . The method according to claim 2 , wherein the concentration of the alkaline solution for washing the pre-carbonized precursor is 0.05-1.0 mol / L.

6. The method according to claim 2, wherein the alkaline solution treatment time is 2-10 hours.

7. The method according to claim 2, wherein the alkaline solution treatment further comprises adjusting the pH value to 6.0-8.

0.

8. An anode of a battery, comprising: A hard carbon material with a molecular sieve-type closed-pore structure.

9. The anode according to claim 8, wherein the molecular sieve type closed-pore structure is formed by: calcining a biomass mixture having 70-90% cellulose, 9-20% hemicellulose and 1-10% lignin at 300-600°C to produce a pre-carbonized precursor; washing the pre-carbonized precursor with an alkaline solution to adjust the pH value to 6.0-8.0; and calcining the pre-carbonized precursor again at 900-1400°C to produce the molecular sieve type closed-pore structure.

10. A battery comprising: cathode; an electrolyte coupled to the cathode; and an anode coupled to the electrolyte, the anode having a molecular sieve type closed-pore structure.

11. The battery according to claim 10, wherein the molecular sieve type closed-pore structure is formed by: calcining a biomass mixture at 300-600°C to produce a pre-carbonized precursor; washing the pre-carbonized precursor with an alkaline solution to wash the pH value to 6.0-8.0; and calcining the pre-carbonized precursor again at 900-1400°C to produce a molecular sieve type closed-pore hard carbon.

12. The battery of claim 11, wherein the biomass mixture comprises 70-90% cellulose, 9-20% hemicellulose and 1-10% lignin.

Citation Information

Patent Citations

  • Biomass-based hard carbon material as well as preparation method and application thereof

    CN116812906A

  • Preparation method of sodium ion battery negative electrode hard carbon material with closed microporous structure

    CN117003237A

  • Preparation method and application of hard carbon taking cotton and hemp biomass as raw material

    CN118047370A

  • Method for preparing hard carbon negative electrode material rich in closed pores from porous carbon and application of hard carbon negative electrode material

    CN118239487A

  • Biomass-based hard carbon material as well as preparation method and application thereof

    CN118289733A

Cited By

  • Hard carbon negative electrode material and preparation method and application thereof

    CN119905585A

  • Sodium ion battery suitable for backup power supply

    CN120319874A

  • Preparation process of sodium ion battery hard carbon-based negative electrode material with high cycle stability

    CN121672472A